2021
DOI: 10.1186/s13098-021-00706-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-care practices and resilience in the Brazilian COVID-19 pandemic: results of a web survey: DIABETESvid

Abstract: Background The world guidance on the measures of social distancing for prevention of COVID-19 has changed the daily habits of great part of the population, and this could influence the care and resilience with diabetes during situations of adversity. This study aimed at assessing the characteristics of diabetic individuals and self-care practices and resilience with diabetes in the context of the COVID-19 pandemic in Brazil. Methods This is a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
(36 reference statements)
0
11
0
2
Order By: Relevance
“…Total studies yielded from databases with the search terms "COVID" and "diabetes" with the following separate search terms: "lifestyle", "health behaviors", "self-care", "self -management", "adherence", "compliance", "eating", "diet", "physical activity", "exercise", "sleep", "selfmonitoring of blood glucose", "SMBG", "continuous glucose monitoring", and "CGM": Eleven studies assessed diet. Several studies reported an increase in unfavorable dietary habits, including decreased dietary adherence (40), high consumption of fatty foods and sweets (39), and increased food intake (43,53). One study reported favorable changes in diet, i.e., increased fruit and vegetables and decreased snacks, fried, or processed foods (58).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total studies yielded from databases with the search terms "COVID" and "diabetes" with the following separate search terms: "lifestyle", "health behaviors", "self-care", "self -management", "adherence", "compliance", "eating", "diet", "physical activity", "exercise", "sleep", "selfmonitoring of blood glucose", "SMBG", "continuous glucose monitoring", and "CGM": Eleven studies assessed diet. Several studies reported an increase in unfavorable dietary habits, including decreased dietary adherence (40), high consumption of fatty foods and sweets (39), and increased food intake (43,53). One study reported favorable changes in diet, i.e., increased fruit and vegetables and decreased snacks, fried, or processed foods (58).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported substance use. For alcohol, Binhardi et al (39) and Ghosh et al (45) reported that modal responses were no alcohol consumption or no change in alcohol consumption, respectively. Hansel et al (47) and Sacre et al (36) reported no change in alcohol consumption.…”
Section: Resultsmentioning
confidence: 99%
“…SDSCA contained 12 questions that were scored based on a seven-point Likert scale. We removed the question on smoking because none of the women and only a few men in our study smoked, and most previous studies also focused on the five main areas and eliminated this item ( Hurst et al, 2020 ; Binhardi et al, 2021 ; Almomani and Al-Tawalbeh 2022 ). Therefore, we used 11 items which assess five aspects of diabetes self-care activities, including diet (4 questions), physical activity (two questions), insulin injection or proper pill taking (one question), blood sugar self-monitoring (two questions), and foot care (two questions).…”
Section: Methodsmentioning
confidence: 99%
“…Considerando a complexidade do diabetes, a necessidade do uso contínuo de medicamentos para o tratamento da doença, bem como os atuais desafios para a integralidade da assistência, tornou-se de grande valia investigar as particularidades do cuidado em diabetes no contexto pandêmico. Neste sentido, o presente estudo faz um recorte da DIABETESvid 12,13 para analisar as fontes de obtenção dos medicamentos para o diabetes na pandemia de COVID-19 no Brasil.…”
Section: Onde Os Brasileiros Obtiveram Os Medicamentos Para O Diabete...unclassified
“…Os dados da presente análise fazem parte da pesquisa DIABETESvid, a qual investigou o autocuidado e a resiliência de pessoas com diabetes na pandemia de COVID-19 13 . Tratase de um estudo transversal conduzido na forma de websurvey, pesquisa realizada pela internet, no período de 1 de setembro a 19 de outubro de 2020 (semanas epidemiológicas 35 a 42).…”
Section: Métodosunclassified